2016
DOI: 10.1111/1365-2745.12524
|View full text |Cite
|
Sign up to set email alerts
|

The importance of autonomous selfing in preventing hybridization in three closely related plant species

Abstract: Summary In plants that are able to self‐fertilize, autonomous selfing has been hypothesized to function as an effective mechanism that prevents heterospecific mating. However, there have only been few studies that have assessed the relative and absolute contribution of different modes of selfing to total reproductive isolation acting between species. Because selfing can be expected to increase fitness costs when offspring are sired from more outcrossing sister taxa, it can be hypothesized that the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 57 publications
1
52
0
Order By: Relevance
“…Brys et al. () similarly found that timing of selfing among Centaurium species was critical to determining the risk of hybridization, with prior selfing clearly serving as the most efficient barrier to hybridization. Our study is unique in demonstrating a general pattern of divergence between allopatric and sympatric populations within a species in the timing of selfing, providing the first evidence for this fundamental signature of reproductive character displacement due to reinforcement (reviewed in Brown and Wilson ; Schluter and McPhail ; Servedio and Noor ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brys et al. () similarly found that timing of selfing among Centaurium species was critical to determining the risk of hybridization, with prior selfing clearly serving as the most efficient barrier to hybridization. Our study is unique in demonstrating a general pattern of divergence between allopatric and sympatric populations within a species in the timing of selfing, providing the first evidence for this fundamental signature of reproductive character displacement due to reinforcement (reviewed in Brown and Wilson ; Schluter and McPhail ; Servedio and Noor ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, autonomous selfing that occurs before opportunities for HPT could be considered a preemptive action that protects against fitness losses through gamete loss to and hybridization with congeners, a hypothesis recently outlined by Brys et al. () that we term the “preemptive selfing hypothesis.”…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because several studies have shown that Epipactis species can rapidly evolve towards selfing (Pedersen and Ehlers , Squirrell et al , Brys and Jacquemyn ) and because selfing itself can act as a reproductive barrier preventing interspecific mating (Brys et al ), we investigated whether the capacity to self autonomously differed between the two ecotypes. Two months before flowering, ten individuals were selected in one forest and one dune population and transferred to a pollinator‐free greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, early selfing might be selected for if it reduces interspecific pollen transfer. In contrast to delayed selfing, earlier selfing can reduce loss of fitness through production of hybrid offspring and would be favored under conditions in which hybridization invokes a high fitness cost (Goodwillie and Ness, 2013;Brys et al, 2016).…”
Section: Evolutionary Stability Of Delayed Selfingmentioning
confidence: 99%